The Role of Remuneration in Improving Budget Implementation Performance: Study at Public Service Agency Universities - Herlina Herlina; Sri Isnowati (Universitas Negeri Semarang, 2023)
The study aims to analyze the effect of understanding financial information systems, competence, understanding of laws and regulations, and training on budget execution performance. The evaluation of budget execution performance is an important indicator of the acceleration and modernization of budget execution in a professional, open, effective, efficient, and responsible manner with the principles of financial management. Additionally, this research also examines whether remuneration serves as a reinforcement or moderation in improving budget execution performance. The research method used is a quantitative approach, analyzing causality between variables. The study used a saturated sample of 117 employees working in the finance sector at Universitas Negeri Semarang. The results of the study demonstrate that only the competency variable has an effect on budget execution performance. The variables of understanding financial information systems, understanding laws and regulations, and training do not have an impact on the performance of budget execution. The research proves that remuneration moderates the effect of competence on budget execution performance. Other variables in this study are not moderated by remuneration on budget execution performance. The research implication is to optimize competence and remuneration to achieve budget execution performance according to planning